Efficiency Assessment of Indian Textile Units Using Data Envelopment and Regression Analysis - Jhaveri, Chetan A.; Sood, Gunjan; Shah, Riya (Indian Journal of Finance, 2021)
Firms are always in the pursuit of improvizing their performance. Optimum utilization of resources and the eradication of sources of inadequacies result in improved performance and production for manufacturing firms. Improved performance and production lead to increased efficiency for the firms. In this study, data envelopment analysis was used to evaluate the efficiency using financial data of 11 years of all the 13 S&P BSE 500 listed textile firms. Consistent with the relevant literature, three inputs (power, fuel, & water charges ; compensation to employees ; and raw materials, stores, & spares) and one output (profit before tax) were selected. Additionally, outcomes from the DEA analysis were used to perform the regression analysis. Out of the 13 units analyzed for efficiency, two textile units were found to be operating efficiently. The results of the regression analysis showed that an increase in employee compensation will lead to an increase in profit since the increase in the compensation helps to increase motivation from job satisfaction. Besides adding value to the efficiency assessment literature, the research findings of this study also provide meaningful business insights for the practitioners for improving productivity performance by finding the core action area in resource planning decisions.